2020
DOI: 10.3390/ijerph17030813
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Varied Factors on Iron, Nickel, Molybdenum and Vanadium Concentrations in the Knee Joint

Abstract: The aim of this study was to determine the concentrations of iron, nickel, molybdenum, and vanadium in the knee joint. We also examined the relationships between the concentrations of these metals in the knee joint and the influence of varied factors on the concentration of Fe, Ni, Mo, and V. The study of these trace elements is important, because these elements are used alone and in combination in diet supplements, and they are components of biomaterials implanted in medicine. The study materials, consisting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 60 publications
(84 reference statements)
0
7
0
Order By: Relevance
“…It is proven in a previous study that the toxicity caused by the accumulation of iron in body tissues can result in cirrhosis, hepatic carcinoma, heart failure, diabetes mellitus, and osteoporosis 16 .…”
Section: Discussionmentioning
confidence: 99%
“…It is proven in a previous study that the toxicity caused by the accumulation of iron in body tissues can result in cirrhosis, hepatic carcinoma, heart failure, diabetes mellitus, and osteoporosis 16 .…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that ferroptosis plays an important role in the pathogenesis of various diseases, including OA [ [31] , [32] , [33] , [34] ]. Iron was not only an essential trace element in human body, but also indispensable for metabolic reactions in chondrocytes, such as redox reactions, cellular respiration and DNA synthesis [ 35 , 36 ]. However, the range of cellular benefits of iron was narrow, and intracellular iron overload in chondrocytes had been suggested as a risk factor for OA [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Iron is a ubiquitous element that participates in many physiological processes. It can promote collagen synthesis and the conversion of 25 hydroxyvitamin D to its active form ( 110 , 111 ). Meanwhile, it stimulates the synthesis of bone matrix by activating lysyl hydroxylase, activates 25 hydroxycholecalciferol hydroxylase and supports the mineralization of bone matrix through vitamin D. Díaz-Castro et al ( 57 ) have found that severe iron deficiency results in poor bone mineralization, alters bone microstructure, reduces bone strength, and decreases biochemical markers of bone formation, such as N-terminal peptide of type I procollagen.…”
Section: Impact Of Eight Trace Elements On Oamentioning
confidence: 99%
“…Nieuwenhuizen et al ( 65 ) have shown that iron overload synovial cells release pro-inflammatory cytokines, such as interleukin-1, interleukin-6, and tumor necrosis factor-α, which trigger the catabolism of chondrocytes. In addition, high level of iron has been found in the infrapatellar fat pads of iron overload animals, which is owing to the accumulation in macrophages ( 111 ). The infrapatellar fat pad plays an important role in the homeostasis of knee joint ( 66 ).…”
Section: Impact Of Eight Trace Elements On Oamentioning
confidence: 99%